Implications of Teacher Life–Work Histories for Conceptualisations of 'Care': Narratives from Rural Zimbabwe. (11th December 2015) - Coultas, Clare; Broaddus, Elena; Campbell, Catherine; Andersen, Louise; Mutsikiwa, Alice; Madanhire, Claud; Nyamukapa, Connie; Gregson, Simon
Abstract: Schools are increasingly seen as key sites for support to HIV‐affected and other vulnerable children, and teachers are assigned the critical role of identifying and providing psychosocial support. Drawing on the life–work history narratives of 12 teachers in Zimbabwe, this paper explores the psychosocial processes underpinning teachers' conceptualisations of these caring roles. The influence of prolonged adversity, formative relationships, and broader patterns of social and institutional change in teacher identity formation processes speak to the complex and embodied nature of understandings of 'care'. In such extreme settings teachers prioritise the material and disciplinary aspects of 'care' that they see as essential for supporting children to overcome hardship. This focus not only means that emotional support as envisaged in international policy is commonly overlooked, but also exposes a wider ideological clash about childrearing. This tension together with an overall ambivalence surrounding teacher identities puts further strain on teacher–student relationships. We propose the current trainings on providing emotional support are insufficient and that more active focus needs to be directed at support to teachers in relation with their students. © 2015 The Authors. Journal of Community & Applied Social Psychology published by John Wiley & Sons Ltd.